'I just thought that it was such an impossible thing': A qualitative study of barriers and facilitators to discontinuing long‐term use of benzodiazepine receptor agonists using the Theoretical Domains Framework - Tom Lynch; Cristín Ryan; Cathal A. Cadogan (Wiley, 2022)
Abstract Introduction Existing interventions to reduce long‐term benzodiazepine receptor agonist (BZRA) use lack theoretical underpinning and detailed descriptions. This creates difficulties in understanding how interventions work and how to replicate them in practice. The Theoretical Domains Framework (TDF) can be used to identify behaviour change determinants to target during intervention development. Objective To explore barriers and facilitators to discontinuing BZRA use from the perspective of both current and previous long‐term BZRA users. Design/Setting and Participants Semistructured TDF‐based interviews were conducted with community‐based individuals with current or previous experience of long‐term BZRA use. Data were recorded, transcribed and analysed using the framework method. Results Twenty‐eight individuals were interviewed. Despite commonalities in perceived barriers/facilitators to discontinuing BZRA use within individual TDF domains, individual participants had different experiences of identified determinants of BZRA discontinuation. For example, both similarities and differences existed within and between each participant group in terms of knowledge of the appropriate duration of BZRA use ('Knowledge' domain) and experience of withdrawal symptoms ('Reinforcement' domain). Compared to previous users, current users typically anticipated more barriers to discontinuing BZRA use and fewer positive consequences of discontinuation. Conclusion This study reports on barriers and facilitators to discontinuing BZRA use from the perspectives of current and previous long‐term users. The findings highlight the challenging nature of BZRA discontinuation and a multitude of barriers that impact participants' behaviour regarding BZRA use. Future work will involve developing a theory‐based intervention to support BZRA discontinuation in primary care. Patient Contribution The study included patients as participants.